TRANSLATING SALAFI-WAHHĀBĪ BOOKS IN INDONESIA AND ITS IMPACTS ON THE CRITICISM OF TRADITIONAL ISLAMIC RITUALS - Munip, Abdul (Balai Penelitian dan Pengembangan Agama Semarang, 2018)
Indonesia is a country with the largest Muslim population in the world and a unique nation that has diversity of tribes, cultures and religions. This uniqueness invites many scholars to observe the religious rituals performed by Muslims in the country. However, scholars do not sufficiently examine the current heated debates about the permissibility of the sacred rituals of Indonesian Muslims. This paper discusses undertakings in translating Arabic books by Indonesian Salafi-Wahhābī scholars and its impact on the increasing criticism against the various rituals practiced by traditional Muslims represented by Indonesian who mainly affiliated to the largest socio-religious organization in Indonesia, Nahdlatul Ulama (NU; the Awakening of Religious Scholars). Using the content analysis, this paper concludes that according to Salafi scholars, the rituals practiced by traditionalist Muslims such as slametan, tahlilan, manakiban and pilgrimage to local Islamic graves are regarded as heretic in the Islamic perspective. On the contrary, according tothe traditionalist Muslims, these rituals, indeed, have a strong foundation in Islam. Facing the Salafi attacks, traditionalist Muslims make various efforts to defend their position and to protect their members from the Salafi influence and criticism. The sharp disagreements between Salafis and traditionalist Muslims are due to a different method in understanding Islam. The former tend to be more puritanical and textual, while the latter tend to be more contextual and adaptive to local wisdom. However, the differences of opinion rarely cause physical conflicts at the grassroots level as Indonesians Muslims have a long experience in maintaining harmony within society.